2018
DOI: 10.26444/aaem/74486
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-economic factors on emotional changes during the postnatal period

Abstract: Objectives. The aim of the study was to identify socio-economic factors that may influence the emotional changes which occur among new mothers in the first days postpartum. Materials and method. A group of 541 women completed a questionnaire consisting of 30 multiple-choice questions, Edinburgh Postnatal Depression Scale (EPDS), and Hospital Anxiety and Depression Scale (HADS). Statistical calculations were performed with the use of Statistica v.10 and Cytel Studio v. 9.0.0. Results. The findings revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…11 There was predominance of puerperal women who did not have their own income for performing unpaid domestic activities or being students (52.6%). These results are in accordance with data found in the literature, which showed that 49.4 to 77.7% 12,14,19,21 of the puerperal women devoted their time to household activities and did not have their own income. Low income was associated with non-adherence to postpartum consultations in the southern region of Brazil 11 ; however, there was no association between income/occupation and adherence to the puerperal consultation in the study sample.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…11 There was predominance of puerperal women who did not have their own income for performing unpaid domestic activities or being students (52.6%). These results are in accordance with data found in the literature, which showed that 49.4 to 77.7% 12,14,19,21 of the puerperal women devoted their time to household activities and did not have their own income. Low income was associated with non-adherence to postpartum consultations in the southern region of Brazil 11 ; however, there was no association between income/occupation and adherence to the puerperal consultation in the study sample.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the puerperal women claimed to be married; however, the rate of women in stable unions was lower than the results of studies conducted in different locations in the country 11,13 and in other countries 16,19 , where the rates go from 70 to 100%. In the literature, the partner's support during the puerperium is signaled as relevant in moments of emotional fragility and uncertainty 9 and is associated with higher scores of mother-baby bond 17 , positive feelings in the puerperium 19 and higher rates of family planning 18,20 , although in this study, the association between having a partner and greater adherence to the consultation has not been proven.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…As mulheres entrevistadas estavam na faixa etária considerada como idade fértil, assim como puérperas que participaram de outros estudos nacionais e internacionais (18)(19)(20)(21)(22)(23)(24) . No entanto, a idade média (25 anos) foi inferior à encontrada em estudos realizados na região sul do país (18) e na Polônia (24) .…”
Section: Discussionunclassified